DEVELOPMENT OF STEM-PjBL BASED WORKSHEET INTEGRATED ENTREPRENEUR CHARACTERISTICS TO IMPROVE CREATIVE THINKING SKILLS - Yulia Pratiwi, Inke; Sutrisno, Sutrisno; Anggeraini, Evita (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The purpose of this development research is to produce an integrated STEM-PjBL-based worksheet product with entrepreneurial characteristics oriented towards students' creative thinking skills in the subject of energy in life. This research is a type of research and development using the 4D model which consists of 4 mutually continuous stages, namely: define, design, develop, and disseminate. STEM-PjBL based worksheet has been developed and validated by material expert validators and media expert validators. Then it was tested on class VII students at SMP N 1 Jambi City. The results of the analysis of science teachers' responses to worksheet obtained an average percentage score of 89.58% which was categorized as "very good". While the results of the student response questionnaire in the small group trial, an average percentage score of 90% was obtained. Then a large group trial was carried out to see the effectiveness of the worksheet. Obtained an average score of students' activity acquisition related to indicators of creative thinking ability experienced an increase. Based on the results obtained in this study it can be concluded that the worksheet developed is feasible to use.